2018
DOI: 10.1002/pri.1719
|View full text |Cite
|
Sign up to set email alerts
|

Description of the CARE4STROKE programme: A caregiver‐mediated exercises intervention with e‐health support for stroke patients

Abstract: BackgroundIntensity of practice and task and context specificity are key factors for improving functional outcome in stroke survivors. Novel methods are needed to augment intensity of practice with minimal use of resources and costs. Caregiver‐mediated exercises (CMEs) focused on mobility, in which a caregiver acts as an exercise coach and can increase the intensity of practice. There is preliminary evidence that CME can improve functional outcome, reduce length of stay, and allow early supported discharge, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“… Both the SHEMA intervention and traditional stroke health education can improve patients’ knowledge of stroke risk factors, but the SHEMA was not superior to traditional stroke health education. Vloothius et al 41 N=7 ∗ Qualitative Netherlands CARE4STROKE Exercise/physical activity/functional mobility To explore how people living with stroke and caregivers managed exercises together. Different role dynamics are at play in caregiver-mediated exercises, and it is important to be aware of possible effects on the strain of patient or caregiver.…”
Section: Resultsmentioning
confidence: 99%
“… Both the SHEMA intervention and traditional stroke health education can improve patients’ knowledge of stroke risk factors, but the SHEMA was not superior to traditional stroke health education. Vloothius et al 41 N=7 ∗ Qualitative Netherlands CARE4STROKE Exercise/physical activity/functional mobility To explore how people living with stroke and caregivers managed exercises together. Different role dynamics are at play in caregiver-mediated exercises, and it is important to be aware of possible effects on the strain of patient or caregiver.…”
Section: Resultsmentioning
confidence: 99%
“…The content of the CARE4STROKE program is reported in accordance with the TIDieR guidelines [19, 20] and has been published elsewhere in more detail. [21] Briefly, the program consisted of 8 weeks of exercise therapy, executed with a caregiver, in addition to usual care following the current guidelines in the Netherlands. [2] The exercise program was composed by a trained physical therapist during weekly sessions.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, informal caregivers often lack knowledge and support and they need more education on how they can provide support with exercise and physical activity [22,23]. Many studies have revealed a need for practical support for stroke survivors and their informal caregivers to help them engage in home-based exercise [10], and recent studies have suggested support could be provided by technical applications [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Technical applications can offer a variety of repetitive and challenging functional tasks [29,31] that can encourage plasticity of the brain and enhance motor learning. Stroke survivors are generally willing to use technical applications to assist with home-based exercise [32][33][34] and many studies have investigated different technical approaches [24,30,35,36]. Virtual reality has been defined as a user-computer interface with real-time simulation and has been shown to increase activity significantly more than conventional therapy [31,37].…”
Section: Introductionmentioning
confidence: 99%